"It's not a very certain future": Emotion and infrastructure change in an industrial town. Issue 132 (June 2022) - Thomas, Gareth; Cherry, Catherine; Groves, Chris; Henwood, Karen; Pidgeon, Nick; Roberts, Erin
Abstract: Four decades on from the onset of deindustrialisation in the UK and other late-capitalist societies, industrial places are again emerging as key objects of policy discourse. Under the dual pressures of decarbonisation, and the recognition of 'left behind' regions as potential hotspots for feelings of political marginalisation, new strategies for clean growth are emerging, aiming to boost local economic and environmental performance. Presenting data produced via biographical interviews and deliberative workshops in Port Talbot, South Wales, we explore how experiences of life in one of the UK's most significant manufacturing towns has shaped local feelings towards four place-based scenarios for industrial and energy systems decarbonisation. Drawing on the rich literatures detailing the cultural and emotional impacts of deindustrialisation, we illustrate how situated experiences of industrial dependence and decline shaped how Port Talbot residents made sense of visions for the town's future. In so doing we show how, in the face of industrial decline, alternative aspects of place emerged as locus points of emotional and cultural identification, 'public things' (Honig, 2017) in which alternative hopes for the future are invested. As emergent policies for clean growth become enacted in concrete projects, we argue for a clearer focus on experiences of and relationships embedded in industrial places, to ensure such strategies meet the desires of local communities.